Spatial Analysis of Vulnerability and Urban Crisis Management with Emphasis on Earthquakes Case Study: Region 2 of Tehran Municipality - Ronak jamshidiy; Pakzad Azadkhani; Tayebeh azizi (اکولوژی انسانی)
One of the strategies for crisis management is spatial analysis and identification of vulnerable areas to reduce damages caused by environmental hazards. The aim of this research is to examine and analyze the preventive role of crisis management in reducing casualties resulting from earthquakes in District 2 of Tehran. This research is applied in nature and employs an exploratory-analytical method. The data and information were collected through documentary and field methods. Data analysis was conducted using ArcGIS software and the TOPSIS model. The study area encompasses the nine districts of District 2 in Tehran. For vulnerability zoning and crisis management, indicators such as the size and dimensions of parcels, building quality, population density, distance from fault lines, and green space availability were utilized. The findings indicate that among the nine districts in District 2 of Tehran, based on the studied indicators, Districts 3, 5, 6, and 8 are the most vulnerable, while Districts 1, 2, 4, and 7 exhibit the least vulnerability. According to the TOPSIS model, the criterion of lack of structural resistance during an earthquake, with a score of 0.6842, has ranked at the top of the evaluated criteria. Therefore, for preventive actions and crisis management aimed at reducing vulnerability before an earthquake occurs, it is essential to prioritize the development of open and green spaces, establishment of crisis management centers, control of population growth in the districts, and enhancement of urban structure modernization and reinforcement.